2014
DOI: 10.1038/ncomms6101
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ protects against EAE by regulating CD4+ T-cell differentiation

Abstract: CD4+ T cells are involved in the development of autoimmunity, including multiple sclerosis (MS). Here we show that nicotinamide adenine dinucleotide (NAD+) blocks experimental autoimmune encephalomyelitis (EAE), a mouse model of MS, by inducing immune homeostasis through CD4+IFNγ+IL-10+ T cells and reverses disease progression by restoring tissue integrity via remyelination and neuroregeneration. We show that NAD+ regulates CD4+ T-cell differentiation through tryptophan hydroxylase-1 (Tph1), independently of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
128
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(139 citation statements)
references
References 62 publications
10
128
0
1
Order By: Relevance
“…This was dependent on glutaminolysis since DON treatment significantly reduced NAD + levels, whereas 2DG treatment increased the NAD + level in Th1/17 cells (Figure S4K). Owing to the well-characterized role of NAD + in regulating T cell proliferation, cytokine production and survival (Bruzzone et al, 2009; Tullius et al, 2014), we determined the impact of modulating NAD + on Th1/17 cell function. We observed that depletion of NAD + using FK866 (Figure S4L), an inhibitor of nicotinamide phosphoribosyltransferase ( Nampt ) that is required for the biosynthesis of NAD + (Bruzzone et al, 2009) resulted in a 2-fold decrease in the frequency of IL17 + IFNγ + population in Th1/17 cells (Figure 4C) and reduced expression of stemness-associated molecules such as Tcf7 , Bcl6 , and β-catenin (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…This was dependent on glutaminolysis since DON treatment significantly reduced NAD + levels, whereas 2DG treatment increased the NAD + level in Th1/17 cells (Figure S4K). Owing to the well-characterized role of NAD + in regulating T cell proliferation, cytokine production and survival (Bruzzone et al, 2009; Tullius et al, 2014), we determined the impact of modulating NAD + on Th1/17 cell function. We observed that depletion of NAD + using FK866 (Figure S4L), an inhibitor of nicotinamide phosphoribosyltransferase ( Nampt ) that is required for the biosynthesis of NAD + (Bruzzone et al, 2009) resulted in a 2-fold decrease in the frequency of IL17 + IFNγ + population in Th1/17 cells (Figure 4C) and reduced expression of stemness-associated molecules such as Tcf7 , Bcl6 , and β-catenin (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…Among all the lineages of CD4+T cells, Th1 and Th17 cells are recognized as critical effector cells responsible for the development of EAE (Tullius et al . ).…”
mentioning
confidence: 97%
“…Like MS, EAE is mainly initiated by aberrant myelin antigen-specific autoreactive CD4+T-lymphocyte invasion into the CNS. Among all the lineages of CD4+T cells, Th1 and Th17 cells are recognized as critical effector cells responsible for the development of EAE (Tullius et al 2014). Th1 cell was long considered to be closely associated to mediate CNS pathology of EAE.…”
mentioning
confidence: 99%
“…However, such studies would probably require a suitable animal model. At present, our work already opens a novel potential therapeutic option as treatment with nicotinamide, in addition to the supplementation of glutamine, it could be considered in future patients with an inherited GLUL defect, possibly also in secondary GS deficiency, and in patients with NAD + aberrations, as this may improve their brain functions and their immunity (Bruzzone et al 2009;Tullius et al 2014).…”
Section: Discussionmentioning
confidence: 99%